Factors associated with participation in continuous professional development activities leading to professional growth of professional nurses working in a public national referral hospital in Namibia. - Mbidi, Tekla Shipahu Natangwe (Stellenbosch : Stellenbosch University, 2018)
Thesis (MNur)--Stellenbosch University, 2018.